Detection of Rare Methyl-CpG Binding Protein 2 Gene Missense Mutations in Patients With Schizophrenia - Chen, Chia-Hsiang; Cheng, Min-Chih; Huang, Ailing; Hu, Tsung-Ming; Ping, Lieh-Yung; Chang, Yu-Syuan (Frontiers in Genetics, 2020)
Deleterious mutations of MECP2 are responsible for Rett syndrome, a severe X-linked childhood neurodevelopmental disorder predominates in females, male patients are considered fatal. However, increasing reports indicate that some MECP2 mutations may also present various neuropsychiatric phenotypes, including intellectual disability, autism spectrum disorder, depression, cocaine addiction, and schizophrenia in both males and females, suggesting varied clinical expressivity in some MECP2 mutations. Most of the MECP2 mutations are private de novo mutations. To understand whether MECP2 mutations are associated with schizophrenia, we systematically screen for mutations at the protein-coding regions of the MECP2 gene in a sample of 404 schizophrenic patients (171 females, 233 males) and 390 non-psychotic controls (171 females, 218 males). We identified six rare missense mutations in this sample, including T197M in one male patient and two female controls, L201V in nine patients (three males and six females) and 4 controls (three females and one male), L213V in one female patient, A358T in one male patient and one female control, P376S in one female patient, and P419S in one male patient. These mutations had been reported to be present in patients with various neuropsychiatric disorders other than Rett syndrome in the literature. Furthermore, we detected a novel double-missense mutation P376S-P419R in a male patient. The family study revealed that his affected sister also had this mutation. The mutation was transmitted from their mother who had a mild cognitive deficit. Our findings suggest that rare MECP2 mutations exist in some schizophrenia patients and the MECP2 gene could be considered a risk gene of schizophrenia.